A Critical Analysis of Challenges and Washback Effects of English Language E-Assessment in Pakistan - Irshad, Asra; Kiani, Zafeer Hussain (Media and Communication Review, 2023)
The use of information technology for assessment especially for educational purposes, is the need of the hour. The major types of e-assessment include multiple-choice tests and evaluation of problem-solving skills. The mode of e-tests is more appropriate and quicker than the outdated paper-based examinations. The application of electronic tests is challenging, especially in a teaching and learning environment. Therefore, this investigation is based on the perceptions of Pakistani students and teachers regarding e-tests along with their washback effects. In addition, the study also examines and explains the various difficulties and trials that Pakistani students face during e-assessment. The sample of the study consisted of 80 BS level English students and 20 EFL teachers from three different universities in Pakistan. Two previously designed questionnaires namely Teachers’ Perceptions and Attitudes Survey (TPAS) and Students’ Perceptions and Washback Effects Survey (SPACES) were adapted as instruments to survey the attitude of students towards e-tests. The obtained data was analysed statistically using SPSS software (IBM 23). The results revealed positive perceptions of Pakistani teachers and learners towards e-assessment. However, the findings also highlighted some negative washback effects and attitudes of the teachers towards e-exams. It is expected that the findings would help the teachers, learners, and policy developers in Pakistan to deduce better results through e-assessment.